STRESS, COPING, ADAPTATION AND CULTURAL DIVERSITY OF HEALTHCARE PERSONNEL - Blumberga, Solveiga; Safonova, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The top priority of medical institutions is to provide quality patient care services. Considering that healthcare personnel are to work with colleagues from various cultures, important are medical personnel training, in-service training, improvement of professional knowledge and skills, ability to adapt to working in a diverse team. The planning of employee training and in-service training is based on the strategic targets and personnel training needs of each institution. Qualification support programmes are organised for medical personnel to improve their professional knowledge and the knowledge and skills of medical nurses in the areas primarily related to patient care, but there is lack of training in stress management and development of stress resistance, as well as facilitation of collaboration with individuals of various cultures. The aim of the research study is to assess the work stress levels of healthcare personnel, the applied work stress management strategies, the levels of social and psychological adaptation of personnel, the ability to adapt to cultural diversity, and their mutual correlations. Research questions: What are the levels of work stress of healthcare personnel? What are the work stress management strategies applied by healthcare personnel? What are the levels of social and psychological adaption of healthcare personnel? What is the ability of healthcare personnel to adapt to cultural diversity? Are there statistically significant correlations between personnel work stress, the applied work stress management strategies, the levels of social and psychological adaptation, the ability to adapt to cultural diversity of the personnel? What exactly should be included in the personnel training plan while preparing the personnel for work in a multicultural environment? The respondents in the research study are healthcare personnel carrying out their duties in Latvia and Scandinavia simultaneously. The following surveys were used for data collection: A Work Stress Scale, a Stress Management Survey, a survey regarding social and psychological adaptation and a Cultural Diversity Self-evaluation Survey. The results of the research study suggest that most of the respondents have low levels of work stress, the active and pro-social management strategies are most frequently used to manage stress, the social and psychological adaptation score corresponds to a medium level. As a result of the research study, the authors prepared recommendations for the Human Resources Department regarding the organisation of training in stress management and development of stress resistance, as well as in the fundamentals of collaboration with individuals of various cultures in order to improve their professional and personal competences.